GENERAL HISTOMORPHOLOGY AND DEVELOPMENTAL CHANGES IN THE OVIDUCT OF KUTTANAD DUCKS (Anas platyrhynchos domesticus) - H. S. Patki; K. M. Lucy; K. R. Harshan; J. J. Chungath (Journal of Veterinary and Animal Sciences, 2010)
Postnatal developmental pattern of the oviduct in Kuttanad ducks was investigated using 78 ducklings from day-old to 24 weeks of age. The material was collected at fortnightly intervals from six birds in each group. Throughout the postnatal period, the structural blue print of the oviduct was seven layered and was devoid of any muscularis mucosa. The mucosa! folds were seen more or less continuous throughout the oviduct, although their height and thickness varied from region to region. Vagina had the thickest tunica muscularis while the infundibulum had the thinnest. The monolayered lamina epithelialis which was made up of ciliated cells and secretory cells, showed two rows of nuclei and was responsible for creating a false impression of cellular stratification. The glandulogenesis as well as the ciliogenesis occurred almost at the same time in almost all the segments of the oviduct.